TIM EBENHAEZER: PEMBINAAN ANAK SEKOLAH MINGGU DAN REMAJA DI GKPA SIPIROK - Siregar, Benget Parningotan; Sakoan, Siskawaty; Manafe, Yanjumseby Yeverson (STT Ebenhaezer Tanjung Enim, 2022)
The Ebenhaezer team is a team formed by students of STT Ebenhaezer (STTE) Tanjung Enim semester IV for the academic year 2021/2022, This is a community service assigned by STT Ebenhaezer to students who practice 5 weeks or between semesters. The team's burden to carry out this program was because they saw the needs of Sunday school children and youth/adolescents as the backbone of the church. So with that, there is a need for coaching for Sunday school children and also for youth/adolescents at GKPA specifically in the Sipirok area so that they can grow in God. Various programs are designed to review children and young people/adolescents in developing their faith in the Lord Jesus, therefore, of course the Team is required to be creative in every program that has been made in order to achieve successful spiritual growth of children and youth.